SYNTHESIS OF THE NOISE IMMUNE ALGORITHM FOR ADAPTIVE CONTROL OF ORE CONCENTRATION - Morkun, V. S.; Morkun, N. V.; Hryshchenko, S. M.; Tron, V. V. (Radio Electronics, Computer Science, Control, 2018)
Annotation Context. Consideration of the transient process characteristics under current industrial conditions, i.e. a controlled object’s static and dynamic characteristics when forming controlling impacts in automatic control systems of ore grinding and sizing is one of the advanced ways to increase their efficiency. Variations in characteristics of initial materials and equipment conditions while changing a command value in closed-loop automatic control systems (ACS) result in transient processes when the granularmetric composition of output products of grinding and sizing aggregates change in a wide range. It leads to additional losses of the recovered grade. Duration of transient processes depends on how the controlled object’s current condition (its static and dynamic characteristics) corresponds to the controller’s adjustment in the ACS. It causes the necessity to readjust the controller’s parameters from time to time that is done in the adaptive ACS to the best advantage. The authors suggest an algorithm of noise immune correction of the controller’s parameters in the closed-loop automatic control system, which is based on preliminary identification of the controlled object’s static and dynamic characteristics in accordance with parameters of the transient process starting in the closed-loop ACS of the transient process. There are determined limits to its applicability at concentration plants. Objective. The research aims to develop a noise immune algorithm of adaptive control over objects with variable static and dynamic characteristics on the basis of the controlled parameter value and the rate of its changes on the initial stage of transient processes in the closed-loop ACS. Method. Current approaches and methods of improving ore concentration control are analyzed to substantiate the research topicality, goals and objectives. The adaptation algorithm for local ACS of ore concentration is synthesized and analyzed by methods of analytical design and computer simulation. Conclusions. The theory of forming specified parameters of transient processes in the closed-loop ACS by means of objects with variable static and dynamic characteristics on the basis of the controlled parameter value and the rate of its changes on the initial stage of these processes is developed in the present research. It allows synthesizing adaptive ACS, in which the error ratio in the transient process reaches zero in a minimum of time without changing its sign subject to disturbances and noises.